Serangga Predator pada Tanaman Padi di Desa Senaning dan Lubuk Ruso, Kecamatan Pemayung, Kabupaten Batanghari - Anjani, Syifa Darma; Ratna, Yuni; Pebrianti, Herni Dwinta (Universitas Batanghari Jambi, 2025)
This study aims to determine the population of predatory insects in rice cultivation in Senaning and Lubuk Ruso Villages, Batanghari Regency. Data collection was carried out 4 (four) times, namely when the rice plants were 7 and 21 days after planting (vegetative phase), and when the rice plants were 56 and 70 days after planting (generative phase) using yellow tray traps, pitfall traps, direct observation and swing nets. In each rice field, 10 sample plots were made with a size of 2 m x 2 m each, which were placed randomly. In each sample plot, 1 (one) yellow tray trap and 2 (two) pitfall traps were placed, then the traps were left for 24 hours in the field. The results showed that the total types of predatory insects in rice crops in Senaning Village consisted of 9 species and 126 individuals, while in Lubuk Ruso Village it consisted of 13 species and 95 individuals. The population of predatory insects is higher in rice cultivation with low pesticide application frequency, close planting distance and rice varieties with more tillers.